ЛИДЕРСКИЕ СПОСОБНОСТИ ЛИЧНОСТИ – КАК НЕОТЪЕМЛЕМАЯ ЧАСТЬ В ОРГАНИЗАЦИОННОЙ ДЕЯТЕЛЬНОСТИ - Сайтбекова, С.; Гайратова, Ш. (SCIENCE and SOCIETY, 2021)
The article talks about the importance of leadership qualities in the formation and development of a comprehensively, competitively capable personality.